Organic Solar Cells: Photochemical Synthesis of Solution‐Processable Graphene Derivatives with Tunable Bandgaps for Organic Solar Cells (Advanced Optical Materials 5/2015). Issue 5 (May 2015) - Stylianakis, Minas M.; Sygletou, Maria; Savva, Kyriaki; Kakavelakis, George; Kymakis, Emmanuel; Stratakis, Emmanuel
<x xml:space="preserve">Abstract</x> The artwork represents the photochemical reaction for the synthesis of a graphene‐based electron‐accepting derivative. Ethylene‐dinitro‐benzoyl small molecules are shown in the vicinity of a graphene oxide nanosheet, one of which is preferentially bonded to the graphene oxide lattice under the photochemical action of a laser beam. On page 658, E. Kymakis, E. Stratakis, and co‐workers use this photochemical synthetic route to create graphene‐based electron acceptors with tunable bandgaps for organic solar cells.